F-18-FDG PET/CT Findings of Myeloid Sarcoma in the Pancreas - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Myeloid sarcoma (MS) is a rare neoplasm of leukemic cells that infiltrates an extramedullary soft tissue. MS may present at initial diagnosis of any myeloproliferative disease or relapse after treatment. It is most commonly associated with acute myeloid leukemia. The incidence of pancreatic involvement of MS is very rare. Herein we present FDG PET/CT findings of a rare case of MS involving the pancreas, which was initially misdiagnosed as pancreatic carcinoma.
Keywords: myeloid sarcoma; pancreas; FDG; Ga-68-DOTATATE; PET/CT; GRANULOCYTIC SARCOMA